2017
DOI: 10.1111/nph.14813
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactone‐triggered stomatal closure requires hydrogen peroxide synthesis and nitric oxide production in an abscisic acid‐independent manner

Abstract: SummaryAccumulating data indicate that strigolactones (SLs) are implicated in the response to environmental stress, implying a potential effect of SLs on stomatal response and thus stress acclimatization. In this study, we investigated the molecular mechanism underlying the effect of SLs on stomatal response and their interrelation with abscisic acid (ABA) signaling.The impact of SLs on the stomatal response was investigated by conducting SL-feeding experiments and by analyzing SL-related mutants. The involvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
109
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(115 citation statements)
references
References 83 publications
(153 reference statements)
5
109
1
Order By: Relevance
“…On the other hand, the transcript levels of the SL‐biosynthetic genes D27 and MAX1 ‐homologues Os01g0701400 , Os01g0700900 , Os02g0221900 , and Os06g0565100 were upregulated in rice shoots, as was observed for SlCCD7 and SlCCD8 in the case of tomato (Haider et al, ; Visentin et al, ). These data were in agreement with the detection of increased transcript levels of SL‐biosynthetic genes MAX3 and MAX4 in the leaves of Arabidopsis upon dehydration (C. V. Ha et al, ) and NaCl and mannitol treatments (Lv et al, ), as well as with the upregulation of the SL‐biosynthetic FaD17 gene in the crowns of tall fescue ( Festuca arundinacea ) and the D10 , D17 , and D27 genes in the base of rice stems under drought stress (Table ; Du et al, ; Zhuang et al, ). Collectively, these findings suggest that the induction of SL synthesis in the aboveground organs of plants is triggered in response to osmotic stress.…”
Section: Sl Production In Plants Under Abiotic Stressessupporting
confidence: 86%
See 3 more Smart Citations
“…On the other hand, the transcript levels of the SL‐biosynthetic genes D27 and MAX1 ‐homologues Os01g0701400 , Os01g0700900 , Os02g0221900 , and Os06g0565100 were upregulated in rice shoots, as was observed for SlCCD7 and SlCCD8 in the case of tomato (Haider et al, ; Visentin et al, ). These data were in agreement with the detection of increased transcript levels of SL‐biosynthetic genes MAX3 and MAX4 in the leaves of Arabidopsis upon dehydration (C. V. Ha et al, ) and NaCl and mannitol treatments (Lv et al, ), as well as with the upregulation of the SL‐biosynthetic FaD17 gene in the crowns of tall fescue ( Festuca arundinacea ) and the D10 , D17 , and D27 genes in the base of rice stems under drought stress (Table ; Du et al, ; Zhuang et al, ). Collectively, these findings suggest that the induction of SL synthesis in the aboveground organs of plants is triggered in response to osmotic stress.…”
Section: Sl Production In Plants Under Abiotic Stressessupporting
confidence: 86%
“…It is worth mentioning that treatment of broad bean ( Vicia faba ) with GR24 enhanced stomatal closure in a concentration‐dependent manner (Y. Zhang et al, ). Very recently, Lv et al () reported that rac ‐GR24 induced the production of H 2 O 2 and NO that were required for promoting SL‐mediated stomatal closure in Arabidopsis . These results may imply a potential crosstalk between SL or SL‐like compounds with H 2 O 2 /NO signalling pathways in regulating plant acclimatization to external stresses (Figure ).…”
Section: Implication Of Sls In Plant Responses and Adaptation To Droumentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the interactions between NO and ABA have been studied, and NO is now considered as an important participant in ABA‐mediated signaling pathways. NO participates downstream in the effects of ABA on processes such as stomata movement and oxidative tolerance . However, there have been few studies of the roles of NO–ABA interactions in chilling stress and antioxidant defense in horticultural plants.…”
Section: Introductionmentioning
confidence: 99%